UNDERSTANDING BODY LANGUAGE AND FACIAL EXPRESSIONS - EGAMBERDIYEVA IRODAXON; ABDULLAJONOV AHRORBEK (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation : This article discusses the roles played by body language in communication, as well as body language examples and the meaning behind them so you know what to look for when you're trying to interpret nonverbal actions.